Tuning of PI controller for coupled-tank liquid level control system using a stochastic search technique [electronic resources] - 227246 Ammar Hussam Yousif Yacoub; Fakulti Kejuruteraan Elektrik (2009)
Thesis (Sarjana Kejuruteraan Elektrik(Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia,2009